Legal Regulation of Circulation of Biocidal Products and Medical Devices in the EU: Implications for the Legal System of Ukraine - Vladyslav Teremetskyi; Yuliya Panfilova; Oleksandr Tkachenko; Yuliia Burchenko; Yuliia Moroz; Ihor Diorditsa; Olesia Batryn (International Journal of Medical Toxicology and Legal Medicine, 2024)
Market volumes and revenues from biocidal products and medical devices grow annually. However, due to safety concerns, many countries have tightened control over their composition and circulation. The purpose of this article is to analyze the legal regulation of the circulation of medical devices and biocidal products, in particular, the requirements for labeling, the procedure for placing on the market, import and export, as well as the procedure for obtaining a permit to introduce biocidal products to the market. In view of the chosen research topic and to achieve the set goal, the authors used general scientific and special methods of scientific knowledge. Measures to control compliance with legal requirements for the safety of medical devices and biocidal products, types of violations in this area and the responsibility of market entities are considered. The relevant legislation of the European Union and the national legislation of Austria, Lithuania, Latvia, Germany, the Netherlands, Poland and Finland are analyzed. Special attention is paid to the regulation of control over compliance with safety requirements and the procedures for obtaining permits for the introduction of biocidal products into the market. It is established that the biocidal authorization procedure is defined in the Regulation on biocidal products (EU) 528/2012 and supplemented in the national legislation of foreign countries. The principles of legislative regulation of the circulation of medical devices are defined in regulations (EU) 2027/745 and 2017/746, which are applied in EU member states and are part of national legislation. It is proved that in most countries there are rules for registration of medical devices and biocidal products, assessment of their safety and efficacy, and control over their use and distribution; databases containing information on the composition, properties, efficacy and safety for health and the environment are formed and functioning; the authorities with controlling powers in the field of circulation of medical devices and biocidal products are identified, and liability for violation of regulations related to circulation of medical devices and biocidal substances is provided. Directions for improving the legal regulation of the circulation of medical devices and biocidal products in Ukraine are proposed.